The carriage of antibiotic resistant Gram-negative organisms in children in the Cape Town community and the impact of antibiotic exposure on the development of resistance (a TB-CHAMP sub-study) - Ocloo, Remous (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.